Flower nectar trichome structure of carnivorous plants from the genus butterworts Pinguicula L. (Lentibulariaceae) - Lustofin, Krzysztof; Świątek, Piotr; Miranda, Vitor F. O. [UNESP]; Płachno, Bartosz J. (Springer Nature, 2019)
Pinguicula (Lentibulariaceae) is a genus comprising around 96 species of herbaceous, carnivorous plants, which are extremely diverse in flower size, colour and spur length and structure as well as pollination strategy. In Pinguicula, nectar is formed in the flower spur; however, there is a gap in the knowledge about the nectary trichome structure in this genus. Our aim was to compare the nectary trichome structure of various Pinguicula species in order to determine whether there are any differences among the species in this genus. The taxa that were sampled were Pinguicula moctezumae, P. moranensis, P. rectifolia, P. emarginata and P. esseriana. We used light microscopy, histochemistry, scanning and transmission electron microscopy to address those aims. We show a conservative nectary trichome structure and spur anatomy in various Mexican Pinguicula species. The gross structural similarities between the examined species were the spur anatomy, the occurrence of papillae, the architecture of the nectary trichomes and the ultrastructure characters of the trichome cells. However, there were some differences in the spur length, the size of spur trichomes, the occurrence of starch grains in the spur parenchyma and the occurrence of cell wall ingrowths in the terminal cells of the nectary trichomes. Similar nectary capitate trichomes, as are described here, were recorded in the spurs of species from other Lentibulariaceae genera. There are many ultrastructural similarities between the cells of nectary trichomes in Pinguicula and Utricularia.
Keywords: Butterworts; Carnivorous plant; Floral micromorphology; Lentibulariaceae; Nectary structure; Pinguicula; Spur; Trichomes